Innovations in Rhinoplasty Anatomy, Photography and Surgical Techniques - Shafy, Motaz H. A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This comprehensive book discusses the field of Rhinoplasty from the basic sciences of anatomy and physiology to detailed assessment and application of surgical techniques. The text highlights the psychological aspects of pre- and post-operative Rhinoplasty, the important relationship between the patient and the surgeon, and finally the technical difficulties that surgeons may experience. Innovations in Rhinoplasty: Anatomy, Photography and Surgical Techniques includes innovative anatomical description of the alar base in relation to the orbicularis oris and the value of the newly discovered rim sill folds and the Inferior Vestibular Bands in alar base surgery. The scientific use of photography in Rhinoplasty which is no longer restricted to medico-legal documentation and pre- and post-operative observations is also discussed throughout the book. Equipment, set up and techniques are made simple and inexpensive so that a high standard photography is achieved by the surgeon or any trained personnel in a surprisingly small area in the office practice. In the surgical section of this clinical resource, simple, innovative conservative surgery to the nasal tip is highlighted as a technique to avoid directly stitching the middle crurae. Recognizing the different types of nasal skin plays a considerable role in alar base and nasal tip surgeries. Surgeons in Rhinoplasty seeking to further develop skills and knowledge in anatomy, photography and surgical techniques will find this book an essential read and resource in their daily clinical practice.
A Guide to the Three-Dimensional Visualization and Examination of the Nose -- Anatomy of the External Nose -- The Weak Areas and Soft Folds in the Nasal Walls -- Significance of the Nasal Attachment to the Orbicularis Oris -- The Seven Types of Nasal Skin: Anatomy and Surgical Significance -- Histological Studies of New Anatomical Structures -- The Anatomy and Physiology of Nasal Respiration -- Anatomical Variations of the Nose -- Introduction -- Standardization of Rhinoplasty Photography -- The Significance of the Light Reflex of the Nasal Margins -- The Rim Sill Test -- Photographic Views of the Nose -- Taking, Filing and Viewing Photographs: The Workflow. Closed versus Open Rhinoplasty: an academic approach -- Clinical Subdivisions and Clinical Varieties of Rhinoplasty -- Clinical Assessment of the Rhinoplasty Patient -- Immediate Pre-operative, Operative and Post-operative Rhinoplasty -- Difficulties Associated with Rhinoplasty -- Psychology of Rhinoplasty -- Surgery of the Four Areas of the Nose -- Surgeries of the Anterior and Lateral Walls -- Surgery of Medial Wall -- Surgery of the Inferior Wall -- Clinical Varieties of Rhinoplasty -- Finesse Rhinoplasty -- The Large Nose and the Bulky Nose: Differences and Surgical Management -- The Deviated Nose and the Crooked Nose: Differences and Surgical Management -- Rhinoplasty of the Fractured Nose: Types and Surgical Management -- Secondary Rhinoplasty.
Keywords: Surgery, Plastic; Otorhinolaryngology; Plastic Surgery; Otorhinolaryngology; Rhinoplasty -- methods; Nose -- anatomy & histology